2008
DOI: 10.1039/b719968f
|View full text |Cite
|
Sign up to set email alerts
|

A novel microfluidic driver via AC electrokinetics

Abstract: A novel ac electrokinetic microfluidic driver based on alternating current electro-osmosis flow induced by asymmetrically capacitance/chemistry-modulated microelectrode arrays has been successfully developed and demonstrated. Asymmetric capacitance modulation (ACM) is made of comb electrode arrays and parts of individual electrode surfaces are modulated/deposited with a SiO(2) dielectric layer. This proposed design can be utilized to shift the optimal operation frequency of maximum velocity to a higher frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…2(c)), 31,32 partial modification of the surface of the electrodes with dielectrics ( Fig. 2(d)), 33 and the use of ACETF. 34…”
Section: •1 Fluid Pumpingmentioning
confidence: 99%
“…2(c)), 31,32 partial modification of the surface of the electrodes with dielectrics ( Fig. 2(d)), 33 and the use of ACETF. 34…”
Section: •1 Fluid Pumpingmentioning
confidence: 99%
“…Recently, AC electroosmotic flow (AC-EOF) has attracted an increasing research interest, and shown great potential for lab-on-a-chip applications, such as fluid pumping (Brown et al 2001;Debesset et al 2004;Kuo and Liu 2008), fluid mixing (Sasaki et al 2006;Kim et al 2007), transportation (Tresset and Takeuchi 2005;Hilber et al 2008), as well as concentration of bioparticles (Wong et al 2004;Bown and Meinhart 2006), with its low-voltage operation (\10 Vrms), and operated frequency below 1 MHz. Basically, AC-induced flow originates from the applied AC voltage to planar electrodes immersed in a liquid electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, considerable efforts have been devoted to the exploration of ACEO based on the concept of travelling-wave ACEO using asymmetric electrode arrays. [4][5][6][7][8][9][10] To be asymmetric, the EO must be non-linear. One of the mechanisms of EO non-linearity is due to ionic concentration polarization (CP).…”
Section: Introductionmentioning
confidence: 99%